Promosi Kesehatan Mental melalui Pelatihan Keterampilan Sosial pada Warga Pondok pesantren - Hertinjung, Wisnu Sri; Partini; Lusi Nuryanti; Nisa Rahmah Nur Anganthi; Intan Pramesti Rochana; Mahasri Shobabiya (Warta LPM, 2024)
Social skills are an important aspect that needs to be developed for students because they are a protective factor in creating mental health. It's just that this is one aspect that is still underdeveloped in students. Social skills can be instilled in individuals in various ways, one of which is through training. This community service activity is in the form of Training for Trainers, which aims to increase the capacity of stakeholders to have higher social skills so that they can become role models for students. Participants involved in this activity were administrators, teachers, and caregivers of 30 students. The training lasted 2 meetings, each 3 hours. The training material includes adolescent dynamics, social skills, and the implementation of social skills through the FRESH values, which is an acronym for Friendly (friendly, likes to make friends), Respect (respect), Empathy (empathy or mutual understanding), Smile (smile or friendly to everyone), as well as Humble (humble and not feeling superior to others). The effectiveness of the training was measured using a questionnaire to determine improvements in FRESH implementation. Data were analyzed using central tendency statistics and described narratively. The results show that there has been an increase in the application of FRESH values among dormitory managers, teachers, and caregivers. This improvement is the key to continuous change towards more comfortable and harmonious conditions in Islamic boarding schools, considering that boarding school managers, teachers, and caretakers are the main role models for students while living in Islamic boarding schools. It can be concluded that social skills training through training for trainers has proven effective in improving the social skills of managers, teachers, and caregivers as role models to be imitated by students.